Historical facts about the Mamluk period in the novel of the Egyptian writer Salah Maaty (Journal of Oriental Studies, 2016)
the article considers contemporary egyptian writer salah Maaty’s novel "hizanat shamail" and historical events which have found reflection in his novel.
Keywords: historical novel; salah Maaty; Mamluks